(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The Todas are a rural tribal community of the Nilgiri plateau of Tamil Nadu. They and their language deserve special interest from the standpoint of ethnology and linguistics, both Dravidian and general. Echo words, folk-tale motifs and narrative devices are among the main topics discussed in the following pages, together with riddles, transport puzzles and, more generally, the important role of the oral transmission of knowledge and (ethno)linguistic techniques and lore. KEYWORDS: Toda, Dravidian languages, echo words, folktales, riddles